2008
DOI: 10.1002/nau.20489
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transforming growth factor β1 gene, basic fibroblast growth factor gene and hydroxyproline in diabetes‐induced bladder dysfunction in a rat model

Abstract: Rats with streptozoticin-induced diabetes mellitus showed significant increase in hydroxyproline, TGF beta1 and bFGF levels in their bladders, which may be an important mechanism inducing diabetic cystopathy. Tadenan could effectively reduce hydroxyproline, TGF beta1, and bFGF levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In our previous studies, we found that P. africanum could reduce the content of Hydroxyproline and improve bladder fibrosis and could decrease the expression of basic fibroblast growth factor (bFGF) and transforming growth factor (TGF). Meanwhile, we found that P. africanum could improve the expression of nerve growth factor (NGF), which may have some relationship with the improved bladder function [7]. In our current study, we planned to find some evidences to prove that the change of oxidative stress in bladder has some relationship with bladder function.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our previous studies, we found that P. africanum could reduce the content of Hydroxyproline and improve bladder fibrosis and could decrease the expression of basic fibroblast growth factor (bFGF) and transforming growth factor (TGF). Meanwhile, we found that P. africanum could improve the expression of nerve growth factor (NGF), which may have some relationship with the improved bladder function [7]. In our current study, we planned to find some evidences to prove that the change of oxidative stress in bladder has some relationship with bladder function.…”
Section: Discussionmentioning
confidence: 92%
“…africanum is now widely used to treat mild and moderate symptomatic benign prostate hyperplasia [13][14][15] and bladder dysfunction due to bladder outlet obstruction [16][17][18]. Previous studies have shown that P. africanum could inhibit the fibroblast hyperproliferation induced by growth factors, especially basic fibroblast growth factor [7]. Additionally, longterm administration of P. africanum extract has a beneficial effect on age-related hypercontractility of the rat bladder by reducing the sensitivity of the bladder to electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-stranded cDNA was obtained from 60 ng of the total RNA using the StrataScript First Strand Synthesis System (STRATAGENE 1 , Cedar Creek, TX) with an oligo dT primer. The sequences of primers were as follows: sense primer 5 0 -CTC AAG GCC AAG CTA CA-3 0 and antisense primer 5 0 -GTG ACT CAA TTC TGC GCT CTA-3 0 for desmin (Ohtsuki et al, 2007a); sense primer 5 0 -TGGGCCAGAGTTCGTCCTCA-3 0 and antisense primer 5 0 -TCGGAGTCCACTTCCCTGTC-3 0 for platelet-derived growth factor-receptor b(PDGF-Rb) (Kondo et al, 2003) 0 -GAGTGAACTGTCGCACCAGA-3 0 and antisense primer CGATCACCAGAACTCAGCAA for Kir 6.1 (Chi et al, 2007); sense primer 5 0 -GCCTCTACCAGTGAGGTTTTGAAG-3 0 and antisense primer 5 0 -ATCTCATCTCTTCTCTTCTGCTCCAGC-3 0 for vWF (Hosoya et al, 2000); sense primer 5 0 -CTT CAC CAT CCA GAA GGA AGA GAC-3 0 and antisense primer 5 0 -CAC TGG TAT TCC ATG TCT CTG GTG-3 0 for platelet endothelial cellular adhesion molecule-1 (PECAM) (Ohtsuki et al, 2007b); sense primer 5 0 -AAAATTATACTCAGTGGCTG-3 0 and antisense primer 5 0 -TTCTAGGATTTTATGCTCTA-3 0 for Ang-1 (Kondo et al, 2003); sense primer 5 0 -GACCGCAACAACGCAATCT-ATGAC-3 0 and antisense primer 5 0 -TGTATTCCGTCTCCTT-GGTTCAGC-3 0 for TGFb-1 (Wissel et al, 2006); sense primer 5 0 -TGCAATAAAATAGAACTCCCAACT-3 0 and antisense primer 5 0 -ATGCTCATGATAATCCGACACC-3 0 for TGFb-R1 (Wissel et al, 2006); sense primer 5 0 -GTCAAACTACAGCT-CCAAGC-3 0 and antisense primer 5 0 -TTTATACTGCCCAGTT-CGTT-3 0 for bFGF (Yongzhi et al, 2007); sense primer 5 0 -CACATAGGAGAGATGAGCTTC-3 0 and antisense primer 5 0 -CCGCCTCGGCTTGTCACAT-3 0 for VEGF (Hoehn et al, 2002); sense primer 5 0 -GCCTTTTGCTTCATCGCTTCC-3 0 and antisense primer 5 0 -AACAAGATTAAAGCAAAAGCCAC-3 0 for occludin (Hosoya et al, 2000); sense primer 5 0 -CCTTCCTGG-ACCACAACATC-3 0 and antisense primer 5 0 -GCCGGTCA-AGGTAACAAAGA-3 0 for claudin-5 (Hosoya et al, 2000); sense primer 5 0 -ACTGCTCTCCTGCTGTTCGT-3 0 and antisense primer 5 0 -TGTCGATTTCAATGGCAGAG-3 0 for claudin-12 (Ohtsuki et al, 2007a); sense primer 5 0 -ACAGCCATGAGGTCAGAGGCT-3 0 and antisense primer 5 0 -ACCTAGAAGACATTGAAGGCATC-3 0 for JAM-1 ; sense primer 5 0 -GCGAGGCATC-GTTCCTAATAAG-3 0 and antisense primer 5 0 -TCGCCACCT-GCTGTCTTTG-3 0 for ZO-1 (Shi and Zheng, 2005); sense primer 5 0 -TCACAGCTGCAGGTGTCACA-3 0 and antisense primer 5 0 -TGCTGTTCTGGGTTGAGGAACT-3 0 for ZO-2 (Shi and Zheng, 2005); sense primer 5 0 -CAATGGGAT-CATGAAACCTG-3 0 and antisense primer 5 0 -GAGGCTGATGAATGGAGAA-3 0 for ABCG2 ; sense primer 5 0 -CTGCTCAAGTGAAAGGGGCTACA-3 0 and antisense primer 5 0 -AGCATTTCTGTATGGTATCTGC-AAGC-3 0 for mdr1a (Hosoya et al, 2000); sense primer 5 0 -CTGGCTTGGTGTGAACTGAT-3 0 and antisense primer 5 0 -AGGCTCTGGCTTGGCTCTAT-3 0 for Mrp1 (Hosoya et al...…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Anamentioning
confidence: 99%
“…The completion of the human genome project and the advance of microarray technology offer a new opportunity to gain insight into global gene expression profiles in NGB. Several clinical researchers have started to examine transcriptional changes in the central nervous system or peripheral nerves following spinal cord injury (SCI) 4–9. Based on our prior works which have shown this concept is acceptable,10,11 we focus on examining transcriptional changes in rat bladder wall tissue following SCI.…”
Section: Introductionmentioning
confidence: 99%